2014
DOI: 10.1161/circulationaha.114.010389
|View full text |Cite|
|
Sign up to set email alerts
|

Heart Failure, Saxagliptin, and Diabetes Mellitus: Observations from the SAVOR-TIMI 53 Randomized Trial

Abstract: iabetes mellitus (DM) adds incremental risk of the development and subsequent exacerbation of heart failure even after adjusting for common risk factors, such as ischemic heart disease and hypertension.1 Although incompletely understood, cardiac metabolic dysregulation of glycolysis and fatty acid oxidation observed in the heart of patients with Background-Diabetes mellitus and heart failure frequently coexist. However, few diabetes mellitus trials have prospectively evaluated and adjudicated heart failure as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
473
0
37

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 643 publications
(520 citation statements)
references
References 41 publications
10
473
0
37
Order By: Relevance
“…In EXAMINE, alogliptin had no effect on the composite events of cardiovascular death and hospital admission for HF on post-hoc analysis (HR: 1.00, 95% CI: 0.82-1.21), and the results did not differ by baseline BNP concentration [49]. In SAVOR -TIMI 53, the increased risk of hospitalization for HF was highest among patients with elevated levels of natriuretic peptides, previous HF or chronic kidney disease [50].…”
Section: Lessons From Leadermentioning
confidence: 91%
See 4 more Smart Citations
“…In EXAMINE, alogliptin had no effect on the composite events of cardiovascular death and hospital admission for HF on post-hoc analysis (HR: 1.00, 95% CI: 0.82-1.21), and the results did not differ by baseline BNP concentration [49]. In SAVOR -TIMI 53, the increased risk of hospitalization for HF was highest among patients with elevated levels of natriuretic peptides, previous HF or chronic kidney disease [50].…”
Section: Lessons From Leadermentioning
confidence: 91%
“…Indeed, these meta-analyses of RCTs with GLP-1RAs may be compared with those of RCTs with DPP-4 inhibitors [9,10], which showed that DPP-4 inhibitors were not associated with any increased risk of HF-related hospitalizations [10] except for saxagliptin [9], mainly because of the results of the SAVOR -TIMI 53 trial [7].…”
Section: Effects Of Liraglutide On Cardiac Function and Cardiovasculamentioning
confidence: 99%
See 3 more Smart Citations